Identifying and assessing risk in men who have a history of violence towards their female partners : a thesis submitted to Massey University in partial fulfilment of the requirements for the degree of Master of Social Work - McMaster, Kenneth James (Massey University, 1997)
The general aim of this study was to explore how workers in National Network of Stopping Violence Services (NZ) Inc./Te Kupenga Whakoati Mahi Patunga member groups assess risk of repeated violence in men accessing stopping violence programmes. Increasingly with implementation of legislation such as the Domestic Violence Act 1995, and increasing referrals from Community Corrections, workers engaging with men who are violent towards their female partners will be increasingly asked to make predictions of current and future levels of risk of repeated violence. These predictions of risk are central to accountability processes developed by National Network of Stopping Violence Services (NZ) Inc./Te Kupenga Whakoati Mahi Patunga. This study reports on risk factors identified within a sample of 373 men accessing a New Zealand based stopping violence programme. A consistency between factors identified within the international literature and within the local sample was found. A survey of workers running stopping violence programmes was undertaken to see if the risk factors that they saw as salient, were consistent with those identified in other research. Twenty-three (23) workers responded to the survey and the results indicate a tendency to focus upon contextual indicators of risk at the expense of dispositional, historical and clinical indicators. The results also show that there are a number of constraints to the thorough assessment of risk in men presenting at stopping violence programmes which include; lack of time, competing demands on time, lack of training in risk prediction, and a lack of consistent tools to undertake the task.
Keywords: Wife abuse; Abusive men; Physical abuse; Domestic Violence Act 1995; Violence prevention programme